2021
DOI: 10.1038/s41598-020-80139-x
|View full text |Cite
|
Sign up to set email alerts
|

First instar larvae of endemic Australian Miltogramminae (Diptera: Sarcophagidae)

Abstract: The first instar larva of a species of the Australian endemic genus Aenigmetopia Malloch is described for the first time, along with the first instar larvae of three other Australian species representing the genera Amobia Robineau-Desvoidy and Protomiltogramma Townsend. Larval morphology was analysed using a combination of light microscopy, confocal laser scanning microscopy and scanning electron microscopy. The following morphological structures are documented: pseudocephalon, antennal complex, maxillary palp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…7A-C This study provides the first comprehensive documentation of the cephaloskeleton of muscid species obtained by confocal laser scanning microscopy (CLSM). Despite earlier evidence of the utility of CLSM in visualizing morphological structures, this powerful tool has rarely been used on immature stages of Diptera (Grzywacz et al, 2014a;Szpila et al, 2016Szpila et al, , 2021Li et al, 2021). The main obstacles are high costs, equipment availability and lack of standard protocols for the preparation and visualization of specimens.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…7A-C This study provides the first comprehensive documentation of the cephaloskeleton of muscid species obtained by confocal laser scanning microscopy (CLSM). Despite earlier evidence of the utility of CLSM in visualizing morphological structures, this powerful tool has rarely been used on immature stages of Diptera (Grzywacz et al, 2014a;Szpila et al, 2016Szpila et al, , 2021Li et al, 2021). The main obstacles are high costs, equipment availability and lack of standard protocols for the preparation and visualization of specimens.…”
Section: Discussionmentioning
confidence: 99%
“…The main obstacles are high costs, equipment availability and lack of standard protocols for the preparation and visualization of specimens. The available protocols for the preparation of material for CLSM turn out to be only basic guidelines, and modifications are often required for individual preparations (Grzywacz et al, 2014; Szpila et al, 2021). Throughout this study, we found that the condition of material, the presence of impurities, previous storage conditions and the time of specimen maceration are critical to a successful CLSM analysis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations